2022
DOI: 10.3389/fimmu.2022.1001201
|View full text |Cite
|
Sign up to set email alerts
|

The role of a key transcription factor PU.1 in autoimmune diseases

Abstract: PU.1, a transcription factor member of the E26 transformation-specific family, affects the function of a variety of immune cells in several physiological and pathological conditions. Previous studies studying the role of PU.1 in pathological conditions have mainly focused on immune system-related cancers, and a series of articles have confirmed that PU.1 mutation can induce a variety of immune cell-related malignancies. The underlying mechanism has also been extensively validated. However, the role of PU.1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…It has recently been suggested that PU.1/ FMS-like tyrosine kinase 3 (FLT3) is a crucial proinflammatory axis in RA that promotes inflammatory features in macrophages and malignant changes in RA fibroblastlike synoviocytes (FLS), contributing to the maintenance of the inflammatory microenvironment and the development of synovitis ( 5). In addition, PU.1-dependent production of IL-9 by T cells, previously demonstrated in other autoimmune diseases (6) and confirmed in our model, strengthens the role of PU.1 and IL-9 in CIA models and supports the immunopathogenic role of IL-9 in RA. The specific self-relevance of PU.1 in multiple cells in RA provides new insights into the pathogenesis of RA and discloses new potential therapeutic targets.…”
Section: The Potential Relationship Between Pu1 and Il-9 In The Devel...supporting
confidence: 90%
“…It has recently been suggested that PU.1/ FMS-like tyrosine kinase 3 (FLT3) is a crucial proinflammatory axis in RA that promotes inflammatory features in macrophages and malignant changes in RA fibroblastlike synoviocytes (FLS), contributing to the maintenance of the inflammatory microenvironment and the development of synovitis ( 5). In addition, PU.1-dependent production of IL-9 by T cells, previously demonstrated in other autoimmune diseases (6) and confirmed in our model, strengthens the role of PU.1 and IL-9 in CIA models and supports the immunopathogenic role of IL-9 in RA. The specific self-relevance of PU.1 in multiple cells in RA provides new insights into the pathogenesis of RA and discloses new potential therapeutic targets.…”
Section: The Potential Relationship Between Pu1 and Il-9 In The Devel...supporting
confidence: 90%
“…DNT cells have been reported to be increased in BD patients, which is consistent with our finding 28 . TFs tightly control cell fate in immune cells and have been implicated in the pathogenesis of autoimmune diseases, such as BATF in arthritis and PU.1 in systemic lupus erythematosus 29 33 . We performed TF footprint analysis to further clarify cell-type-specific trans-regulatory elements in BD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liang et al [35] found that Osteoblast differentiation and bone formation in AS may be regulated by STAT3 and SPI1 through MAPK signaling pathway, JAK/STAT and Wnt receptors, and interestingly, GSEA results showed that DYSF is highly enriched in MAPK signaling pathway, and the strong correlation between STAT3 and DYSF suggests that DYSF in AS in ammatory response may likewise play an important role. The SPI1 gene encoding PU.1 has been shown to affect the differentiation and function of multiple myeloid cells [36][37][38][39], It plays a key role in the human immune system and has been shown to be involved in the pathogenesis of many immune-related tumor diseases [40,41]. Recently, many researchers have found that PU.1 plays an important role in the transcriptional control of certain immune cells and the susceptibility to immune diseases.…”
Section: Discussionmentioning
confidence: 99%